Kadar Estradiol pada Sapi Perah Saat Estrus dan Asosiasinya dengan Kebuntingan dan Keragaman Genotipe - Yuliati Wahyu Setyorini; Edy Kurnianto; Sutopo Sutopo; Sutiyono Sutiyono (Universitas Bengkulu, 2023)
This study determined estradiol concentrations during estrous in dairy cattle and its association with pregnancy and genotype diversity. A total of fifteen female dairy cows that had been identified with their genotype type using the PCR-RFLP method on follicle-stimulating hormone receptor (FSHR) and prolactin (PRL) genes were used in this study. The parameters measured were serum estrogen concentrations during estrous, estrous intensity, and pregnancy. Estradiol concentrations were analyzed by the enzyme-linked immunosorbent assay (ELISA) method. The data were analyzed using a general linear model procedure in the SAS program. The results showed that the average estradiol concentrations in dairy cows during estrous were 60.06±33.25 pg/ml. There was no difference (P>0.05) in estradiol concentrations in different classifications of age, body condition score (BCS), and estrous intensity. Estradiol concentrations in the group that showed success in post-insemination pregnancy were higher and significantly different (P<0.05) from the non-pregnant group. Differences in genotype variations of the FSHR and PRL genes had no significant effect (P>0.05) on the estradiol concentrations. In conclusion, estradiol concentrations during estrous were not associated with age, BCS, estrous intensity, and genotype diversity of FSHR and prolactin genes but were associated with pregnancy.